Analyze Constructivist Learning Experiences, Democratic Attitudes, Learning Independence, Students' Learning Motivation - Nurmiah Muin (Postgraduate, University of Mataram, 2025)
The aim was to analyze the constructivist learning experience, democratic attitude, learning independence, and students' motivation. The research subjects consisted of 116 students from the Indonesian language and literature education study program. The research method is a descriptive survey using a closed questionnaire instrument and a Likert scale. The data collection technique is using Google Forms. The data collected were then analyzed using descriptive quantitative and inferential analysis. The results showed that constructivist learning experience was 68% with a low category, democratic attitudes were 79% with a fairly category, learning independence was 71% with a fairly category, and learning motivation was 69.00% with a low category. Then, the very low correlation coefficient value is shown in the constructivist learning experience with a learning motivation of 0.263 with a very low correlation. The high correlation coefficient value on motivation with learning independence is 0.577. The findings of this study indicate that overall, constructivist learning experience, democratic attitudes, learning independence, and student motivation are still and need to be optimized for learning effectiveness.